Electrochemical Microfluidic Platform for Simultaneous Multi-analyte Detection. (2015) - Kling, A.; Dincer, C.; Armbrecht, L.; Horak, J.; Kieninger, J.; Urban, G.
Abstract: We present an electrochemical lab-on-a-chip (LOC) platform for the simultaneous detection of up to four different analytes. The possibility to separately immobilize different assays in a channel network, without active valves, was successfully demonstrated using a model assay linked to glucose oxidase. This enables the detection of various analytes even with different assay formats. For the assay immobilization, the channel surface, made out of dry film photoresist (DFR), could be activated by means of EDC/NHS-linker chemistry and used for the covalent binding of primary amines. Cross-sensitivity due to diffusion within the channel network could be experimentally excluded.